Role of pilocarpine to prevent radiation induced xerostomia in locally advanced head and neck squamous cell cancer (Bangladesh Medical Journal Khulna, 2025)
Background: Radiotherapy of head and neck region generally includes irradiation of the salivary glands. That results in glandular dysfunction which leads to xerostomia. Xerostomia, the subjective sensation of dry mouth which significantly deteriorates the quality of life. Aim and objective: To compare the effects of pilocarpine HCL with basic oral care vs only basic oral care for controlling xerostomia in patients with locally advanced Head and neck squamous Cell Carcinoma patients having definitive concurrent chemoradiotherapy. Material and Method: A prospective observational hospital based study was carried out in the Department of Oncology, Khwaja Yunus Ali Medical College & Hospital from July 2017 to June 2018 on sixty patients of locally advanced HNSCC. All the patients received 66 Gy/33 Fraction/6.5 wks with concurrent weekly cisplatin (40mg/m²). The study group received concomitant Pilocarpine HCL 5 mg three times a day, starting three days prior to start of radiotherapy, continued for 3 months. Patients were evaluated before start of treatment, weekly during radiotherapy and after completion of radiotherapy two weekly over telephone upto 3 months and finally at 6 months using Zimmermen Xerostomia Questionnaire with Visual Analogue Scale and Xerostomia Grading Scale. Result: Overall incidence of xerostomia was significantly lower in pilocarpine group (p